1D.04: INVERSE RELATIONSHIP BETWEEN AORTIC ROOT DIAMETER AND RENAL FUNCTION IN HYPERTENSIVE SUBJECTS. (June 2015) - Mulè, G.; Nardi, E.; Morrcale, M.; D'Amico, S.; Geraci, G.; Nardi, C.; Cerasola, G.; Cottone, S.
Abstract : Objective: Recent studies suggest that enlarged aortic root diameter (ARD) may predict cardiovascular events in absence of aneurysmatic alterations. Little is known about the influence of renal function on ARD. Our study was aimed to assess the relationships between glomerular filtration rate (GFR) and ARD in hypertensive subjects. Design and method: We enrolled 611 hypertensive individuals (mean age: 52 ± 15 years; men 63%) consecutively attending our outpatient unit of Nephrology and Hypertension. Patients on dialysis treatment, with valvulopathy more than mild, bicuspid aortic valve, previous cardiovascular events and genetic aortic diseases were excluded. All the subjects underwent echocardiography. ARD was measured at the level of Valsalva's sinuses by M-mode tracings, under two-dimensional control. In line with the PAMELA study, ARD, ARD indexed to body surface area (ARD/BSA) and to height (ARD/H) were considered increased when they exceeded 3.8 cm, 2.1 cm/m2, 2.3 cm/m in men and 3.4 cm, 2.2 cm/m2, 2.2 cm/m in women, respectively. GFR was estimated by the CKD-EPI equation. The study population was categorized in seven groups: subjects without chronic kidney disease (no CKD) and subjects with increasing severity of CKD (1, 2, 3a, 3b, 4, 5), according to KDIGO classification. Results: Estimated GFR (eGFR) was lower in subjects with values of ARD, ARD/BSA and ARD/H above the sex-specific cut-offs when compared to those with normal aortic root size (all p < 0.001). The analysis of the distribution ARD/BSA in subjects with and in those without CKD, showed a progressive increase of ARD/BSA from the group with normal renal function to the groups with greater severity of CKD (figure). eGFR correlated significantly with ARD (r = - 0.17), ARD/BSA (r = - 0.43) and ARD/H (r = - 0.40; all p < 0.001). The associations of eGFR with ARD/BSA (β= - 0.23) and ARD/H (β= - 0.17; all p < 0.001) held in linear multiple regression analyses, after adjustment for various confounding factors. Figure. No caption available. Conclusions: Our study seems to suggest that a reduced renal function may adversely influence ARD. This may contribute to explain the enhanced cardiovascular risk associated with renal insufficiency.